Marketing roles of university technology transfer offices: a systematic review - Sousa, Dalton de; Zambalde, André Luiz; Brito, Mozar José de (Revista de Administração da UFSM, 2019)
This paper seeks to understand the marketing roles in studies on universities to market technology transfer processes and relies on the fact that universities play a key role in the technological development of a nation. To this end, a systematic review was performed from the Web of Science portal, which generated as a result forty articles. It was found that no periodic dedicated to the marketing item presented on the subject, as well as any of the articles was evaluated based on the marketing theories. Thus, gaps have been identified for research in marketing in this context as well, pointing to negligence of marketing researchers in a theme as relevant for today's world. As an essential consideration, it was found that marketing can contribute to the improvement process of practices that foster innovation in universities in various ways, as in understanding the internal relationships in the institutions, in partnership with these institutions internal and external actors, in promoting technologies and the development of channels with the market, the performance of the developed actions and their results, among other aspects.